DESIGN OF INTERVENTION PREVENTION STRATEGY FOR DIABETES MELLITUS ACCORDING TO SEGMENTATION OF BANDUNG POPULATION BASED ON ANALYSISINTENTION FACTORS OF PHYSICAL ACTIVITY - Pranata Sembiring, Daniel
Diabetes mellitus is a non-communicable disease that rapidly increase in the numbers in the last 20 years. Diabetes was ranked seventh as the highest cause of global death in 2016 which was caused by the triple-burden of health problems. In Bandung, diabetes has continued to grow until it becomes one of the five highest causes of death. This increase is a threat to Bandung citizen health. Lifestyle changes are considered to reduce the risk of diabetes, especially diet and physical activity changes. Physical activity is a risk factor for diabetes. People who lack physical activity indicate a high risk of diabetes. The lack of intervention in increasing physical activity is one of the reasons. To determine the segmentation of Bandung, an intentional model of physical activity is developed based on the Integrated Behavioral Model (IBM) framework. Model development was formulated with nine research hypotheses. The theoretical model was tested using a sample of 226 respondents. Data were processed and analyzed using structural equation modeling to determine the causal relationship among variables and latent class clustering to form segmentation. There are three different clusters distinguished based on opinions on physical activity and demographic characteristics. Segmentation resulted from this research was used as the basis to propose a communication strategy for diabetes prevention interventions designed to increase the frequency of physical activity in Bandung. For each cluster. strategies were built by determining communication’s target audience, goals, channels, and activities that affect the intention to do physical activity.